Repaying Microcredit Loans: A Natural Experiment on Liability Structure. Issue 6 (2nd June 2020) - Mahmud, Mahreen
Abstract: This paper utilises a natural experiment – the shift from individual to joint lending by a microfinance organisation in Pakistan – to show significant improvement in borrower discipline under joint liability loans. I find that a possible mechanism for this impact is the degree of pre-existing social connection between the group members. For the mechanism analysis, I use the exogenous variation in the number of months borrowers had till the expiry of their individual liability loans at the time of the announcement of the shift to joint leading as an instrument for the degree of social connection of the group.